Upper Extremity Injuries Due to Work Accidents in Work Accident Disability Assessments: Three Case Reports - Kılıç, Serbülent; Adıyaman, Sündüz; Sezer, Fatih; Cantürk, Gürol (The Bulletin of Legal Medicine, 2017)
Industrial accident is an area that forensic specialists expertise on. The courts in different cities asked for reports about three injury cases due to industrial accidents from our department of forensic medicine. Each report should include the disability rate and the duration of unfunctionality.The history and physical examination of each case revealed the diagnosis of upper extremity injury due to industrial accident. The first case had few amputations on the hand fingers, and the other cases had paralysis and ancylosis.Industrial accident, a significant problem of public health can causes loss of labour and money, disabilities and even death. Injuries of the upper extremity with the characteristic injury findings are often come across in such accidents. Our aims to present the current three cases are to have forensic medicine specialists be aware of characteristic signs of industrial accidents and the importance of the expert reports preparation concerning industrial accidents.
Keywords: forensic medicine; amputation; hand injury; industrial accident; disability; upper extremity injury